Study of Transformational Leadership, Employee Well-Being and OCB on Performance mediated by Job Satisfaction - Weny Ratna Dewanti; Karsim; Maria Christiana Iman Kalis; Ilzar Daud (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
Teachers must not only provide a good education, but they must also have the quality to perform their duties as learners. Performance becomes one of the main factors determining whether organizations can achieve their goals. This study examines how transformational leadership, well-being, and OCB affect performance through job satisfaction as an intervention variabel. The study used a saturated sampling technique on 60 Al-Fityan Kuburaya Junior High School teachers. Smart PLS 3.0 is used for data management. Convergent validity, discriminant validity and reliability are the measurement models that are utilized. The findings indicate that transformational leadership, employee well-being, and organizational citizenship behavior favorably and substantially impact job satisfaction. However, transformational leadership, employee well-being, and OCB have no significant impact on performance. Thus, job satisfaction can mediate employee well-being, transformational leadership, and OCB on performance.